2020
DOI: 10.1371/journal.pone.0239212
|View full text |Cite
|
Sign up to set email alerts
|

Total body water by BIA in children and young adults with normal and excessive weight

Abstract: Background Estimation of total body water (TBW) is essential for clinical care. Objective Evaluation of changes in TBW by bioelectrical impedance analysis (BIA) in children and young adults with excessive weight. Design Data was collected in individuals aged 3-21 years with normal (n = 202) or excessive body weight (n = 133). The BIA results from individuals with normal weight were compared with two previously published studies in children by isotope dilution methods. Results Individuals with excessive weight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 52 publications
2
13
1
1
Order By: Relevance
“…Our data indicated differences in all of the considered indices, including ICW, ECW, TBW, ICW/TBW, ECW/TBW, and TBW/BW, between all the men and women. Consistent with a study conducted among young adults under free-living conditions, many aspects of body composition, including ICW, ECW, and TBW, differed significantly between men and women ( 20 , 27 , 71 ). One study conducted among children has confirmed similar differences between genders, showing that girls have lower TBW and TBW/BW than boys ( 26 ).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Our data indicated differences in all of the considered indices, including ICW, ECW, TBW, ICW/TBW, ECW/TBW, and TBW/BW, between all the men and women. Consistent with a study conducted among young adults under free-living conditions, many aspects of body composition, including ICW, ECW, and TBW, differed significantly between men and women ( 20 , 27 , 71 ). One study conducted among children has confirmed similar differences between genders, showing that girls have lower TBW and TBW/BW than boys ( 26 ).…”
Section: Discussionsupporting
confidence: 84%
“…Furthermore, in the COVID-19 era, the highest ECW/TBW has been observed in older adults with osteosarcopenic adiposity syndrome (OSA), indicating a heightened inflammatory state ( 19 ). As has been described previously, body composition data are useful for assessing diverse disease conditions; furthermore, they have been associated with physiological status among healthy people ( 20 25 ).…”
Section: Introductionmentioning
confidence: 94%
“…Moreover, the correlation between HC and TBW was considered low, although significant. Mattoo et al, 2020 [ 51 ] also suggested that there is a BM decrease related to TBW, which results from a lower % BF. KASHIWAZAKI et al, 1996 [ 52 ] studied the prediction equations for total body water and concluded that was necessary to include skinfold measurements together the equation to obtain a valid evaluation for males and females (RAISON et al, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…For example, female collegiate athletes were found to drink more and compensate for sweat rates during indoor practice, indicating that drinking may need to be encouraged when practicing outdoors [43]. In other work adults with excessive body weight have been found to store more 'total body water' for height and age than those of normal weight, indicating that hypohydration risk is greater amongst these individuals [44]. Recent work assessing hydration status across three European countries showed that men…”
Section: Discussionmentioning
confidence: 99%